2007
DOI: 10.1124/mol.107.037218
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Splice Variants in the Dioxin-Resistant Rat: Tissue Expression and Transactivational Activity

Abstract: The AHR locus encodes the aryl hydrocarbon receptor (AHR), a transcriptional regulator of multiple drug-metabolizing enzymes and mediator of toxicity of dioxin-like chemicals. The Han/ Wistar (Kuopio) rat strain (H/W) is remarkably resistant to lethal effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) because of a point mutation in the exon/intron 10 boundary in AHR genomic structure that leads to use of 3 alternative cryptic splice sites, potentially creating 3 alternative transcripts and 2 protein product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…4). However, AhRdv was found to have the highest activity mediated by the synthesized XRE among the four AhR variants protein encoded by AhR hw/hw could regulate the XREdependent pathway differently from the proteins encoded by the other AhR variants, which is consistent with the recent data of Moffat and coworkers (Moffat et al, 2007), who showed, using the transactivation domain of AhR variants and the GAL4-DNA binding domain, that -ity in the absence of exogenous ligands such as TCDD.…”
Section: Discussionsupporting
confidence: 81%
“…4). However, AhRdv was found to have the highest activity mediated by the synthesized XRE among the four AhR variants protein encoded by AhR hw/hw could regulate the XREdependent pathway differently from the proteins encoded by the other AhR variants, which is consistent with the recent data of Moffat and coworkers (Moffat et al, 2007), who showed, using the transactivation domain of AhR variants and the GAL4-DNA binding domain, that -ity in the absence of exogenous ligands such as TCDD.…”
Section: Discussionsupporting
confidence: 81%
“…B. Okey, manuscript in preparation). There are dmd.aspetjournals.org substantial differences in AH receptor structure between C57BL/6J mice and wild-type rat AHR (Moffat et al, 2007b;Okey, 2007). To determine whether these differences underlie the lack of FMO induction in rats we measured FMO2 and FMO3 mRNA levels in TCDDtreated transgenic mice that express wild-type rat AHR in a C57BL/6J background.…”
Section: Resultsmentioning
confidence: 99%
“…Among HAHs, ligand affinity is a good predictor of toxicity; compounds that bind with greatest affinity are the most potent at altering gene expression and causing toxic effects (Safe, 1994). Differences in AHR properties, including affinity for ligand binding, explain differences in sensitivity to DLCs in several vertebrate systems, including strains of rodents (Moffat, Roblin, Harper, Okey, & Pohjanvirta, 2007; Poland, Palen, & Glover, 1994), species of birds (Farmahin et al., 2013; Karchner, Franks, Kennedy, & Hahn, 2006), and populations of some fish (Atlantic tomcod) (Wirgin et al., 2011). (At the extreme end of this spectrum are invertebrates, which have AHR proteins that lack the ability to bind DLCs [Powell‐Coffman, Bradfield, & Wood, 1998; Butler, Kelley, Powell, Hahn, & Van Beneden, 2001] and also are largely insensitive to DLC toxicity [Hahn, 1998a]. )…”
Section: Ahr Pathwaymentioning
confidence: 99%